1997
DOI: 10.1046/j.1365-3180.1997.d01-53.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed communities of winter wheat as influenced by input level and rotation

Abstract: Summary The influence of cropping systems constituted by the combination of three input levels (low, intermediate and high) and four 2‐year rotations between a spring summer crop and winter wheat (Triticum aestivum L.) on the density and composition of the winter wheat weed flora was evaluated from 1989 to 1992. Spring summer crops were maize (Zea mays L.). soyabean (Glycine max (L.) Merr.). sugar beet (Beta vulgaris L.) and sunflower (Helianthus and L.) Total weed density at the end of the wheat tillering sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 13 publications
7
60
0
3
Order By: Relevance
“…Intensification of agricultural production, related to the simplifications in the crop structure, and the large use of mineral fertilization and other means of production, mainly herbicides, can reduce weed diversity (Dyer 1995;Barberi et al 1997;Doucet et al 1999). The research results showed a similar number of species accompanying spring wheat in both the integrated and conventional systems.…”
Section: Discussionmentioning
confidence: 99%
“…Intensification of agricultural production, related to the simplifications in the crop structure, and the large use of mineral fertilization and other means of production, mainly herbicides, can reduce weed diversity (Dyer 1995;Barberi et al 1997;Doucet et al 1999). The research results showed a similar number of species accompanying spring wheat in both the integrated and conventional systems.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of weed control was not surprising since application of herbicides was shown to be an important factor previously (Hald 1999, Hyvönen and Salonen 2002, Hyvönen et al 2003. In contrast, the effect of crop rotation has often been shown to be weak (Bàrberi et al 1997, Andersson and Milberg 1998, Doucet et al 1999, unless grasslands are included in the rotation (Paatela andErviö 1971, Sjursen 2001). Evidently, organically cropped fields had more diverse crop rotation histories than conventionally cropped fields.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, southern and south-western Finland are characterized by a high dominance of cereal crops in rotation whereas in central and eastern Finland the use of arable land is more diverse, many farms practising crop rotation based on grassland for silage and hay and pasture for cattle. Since this diversity of crop rotation has been found to have some effect on the species composition (Bàrberi et al 1997) and species diversity (Doucet et al 1999) of weed communities, we expected to find differences between regions.…”
Section: Salonen J Et Al Weeds In Spring Cereals In Finlandmentioning
confidence: 92%